2006
DOI: 10.1038/sj.npp.1301256
|View full text |Cite
|
Sign up to set email alerts
|

The Allosteric Potentiation of Nicotinic Acetylcholine Receptors by Galantamine Ameliorates the Cognitive Dysfunction in Beta Amyloid25–35 I.c.v.-Injected Mice: Involvement of Dopaminergic Systems

Abstract: Galantamine, a drug for Alzheimer's disease, is a novel cholinergic agent with a dual mode of action, which inhibits acetylcholinesterase and allosterically modulates nicotinic acetylcholine receptors (nAChRs), as a result stimulates catecholamine neurotransmission. In the present study, we investigated whether galantamine exerts cognitive improving effects through the allosteric modulation of nAChR in the intracerebroventricular beta amyloid (Ab) 25À35 -injected animal model of Alzheimer's disease. Galantamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(84 citation statements)
references
References 33 publications
5
74
0
5
Order By: Relevance
“…Novel Object Recognition Test-The task was carried out according to previous publications (27,28). The experimental apparatus consisted of a Plexiglas open-field box (40 ϫ 40 ϫ 29 cm).…”
Section: Methodsmentioning
confidence: 99%
“…Novel Object Recognition Test-The task was carried out according to previous publications (27,28). The experimental apparatus consisted of a Plexiglas open-field box (40 ϫ 40 ϫ 29 cm).…”
Section: Methodsmentioning
confidence: 99%
“…Eight of 13 participants were rated as responders on the basis of their improvement scores on the Clinical Global Impressions scale. The allosteric properties of galantamine could directly lead to increased release of acetylcholine and activation of postsynaptic nAChRs (Samochocki et al, 2003) or act indirectly through its effects on the release of other neurotransmitters, especially glutamate and dopamine (Schilström et al, 2007;Wang et al, 2007). It has been demonstrated that amyloid- precursor protein (APP) is upregulated in a mouse model for Fragile X mental retardation (FXS) (Westmark et al, 2008) and two clinical studies have reported higher levels of APP in children with autism.…”
Section: Positive Allosteric Modulatorsmentioning
confidence: 99%
“…Donepezil is a centrally acting selective, competitive, and reversible acetylcholinesterase inhibitor (3). Galantamine, a tertiary alkaloid extracted from the several species of Amaryllidacae, is an acetylcholinesterase inhibitor that also acts as an allosterically potentiating ligand on nicotinic acetylcholine receptors (4,5). On the other hand, memantine is well known to act as an antagonist on Nmethyl-D-aspartic acid (NMDA) receptors and has a protective effect against neuronal damage induced by excess glutamic acid (6).…”
Section: Introductionmentioning
confidence: 99%